The epidemiological characteristics of liver disease in hospitalized children: a 10-year single-center retrospective study - Chen, Fan; Huang, Yuan; Huang, Zhihua; Fang, Feng; Zhou, Hua; Shu, Sainan (Frontiers in Pediatrics, 2024)
Background: This investigation aimed to examine the epidemiological characteristics of children with liver disease hospitalized for the first time between June 2012 and May 2022 in a tertiary hospital.The study retrospectively recruited children aged between 29 days and 18 years who had been hospitalized for liver disease. Clinical characteristics were categorized by age and etiology, and time trends were assessed using linear regression analysis.Results: A total of 4,313 children were recruited, with a median age of 0.7 (0.2-4.5) years, and 54.5% of the cases were in the 0-1 years age group. Infection was the primary cause of liver disease (30.0%), followed by undiagnosed cases (25.8%), biliary obstructive disease (15.9%), inherited metabolic liver disease (13.9%), and nonalcoholic fatty liver disease (NAFLD) (3.2%). Genetic diagnoses were established in 43.9% (478/1088) of patients. The percentage of NAFLD demonstrated an upward trend from 1.2% in 2012 to 12.6% in 2022 (p=0.006). In contrast, the percentage of cytomegalovirus hepatitis decreased from 13.3% in 2012 to 3.4% in 2022 (p=0.002).Conclusions: Liver disease in infancy makes up the largest group in pediatric liver disease. Infection remains the leading cause of pediatric liver disease. Hospital admissions for NAFLD in children have increased rapidly over the past decade, while cytomegalovirus hepatitis has declined markedly.